PENGGUNAAN RASIO KEUANGAN UNTUK MENILAI KINERJA APBD PEMERINTAH KABUPATEN PAMEKASAN TA 2013 s/d 2015 - Rahman, Fadali (Universitas Trunojoyo Madura, 2017)
The Purpose of Â this research are: To assess budget performance district Â ofPamekasan government through success as accountability of financial management area in fiscal year 2013 s/d 2015Â This research shows that the ratio of local financial independence is still relatively very low with an average of 14.62 % score 25, with performance category is not good . The ratio of the effectiveness of local revenues are very effective because each year the percentage ratio is more than 100 %, with an average of 122.03 % had scores 76 with excellent performance categories . Activities ratio : the ratio of recurrent expenditure on average 78.48 % the scoring 76 with excellent performance and development expenditure ratio average of 18.12 % score 25 the performance is not good . Debt Service Coverage Ratio of average 32.29 % score 50 with sufficient performance and the ratio of growth average of 37.86 % score 50 with sufficient performance